Economic Perspective on The Influence of The Power Mode of Wheeled Vehicles of Category N2 on Pollutant Emissions - Maciej GLINIAK; Beata CHUDY; Arkadiusz BIESZCZAD; Piotr JASIŃSKI (Communications of International Proceedings, 2023)
The aim of this study was to compare the exhaust emissions of the current fleet and modernized to Euro VI with a fleet consisting of 50 hybrid cars "Fuso Canter 7C15 HEV Eco Hybrid" and 39 pieces of "Fuso Canter 7C15 HEV" with a fully hybrid fleet consisting of the "Fuso Canter 7C15 HEV Eco Hybrid" and an all-electric fleet consisting of the latest electric trucks presented to the world in autumn 2021 "Volvo FL Electric" and "DAF LF Electric".
Keywords: power mode; vehicles; emission; transport